Diversity and Epidermal Characteristic of Lauraceae Leaf in Two Forest Locations, Bogor Regency, West Java - Nurul amalia fadhila; Sulistijorini Sulistijorini; Nina Ratna Djuita (UIN Sunan Gunung Djati Bandung, 2023)
Lauraceae is a group of tropical plants with a wide distribution. The abundance and species richness of the Lauraceae family includes the under to the upper canopy of the forest. The Lauraceae family can be utilized in various sectors, especially economically. Limiting characters as a significance in the Lauraceae classification was needed to provide additional information regarding taxon grouping. This research aimed to study epidermal characteristics, leaf venation variations, and the diversity of Lauraceae species under different forest environmental conditions. The research procedure involved: collecting ecological field data and morphological identification using a purposive sampling method based on the presence of species. Soil sampling and environmental microclimate were measured on each plot. The anatomical process was carried out by recording characters. Correlation between environmental factors and plant targets used canonical correspondence analysis. The kinship between members of Lauraceae was expressed in a dendrogram. The result of this study showed that Lauraceae could live at various elevations. The analysis data indicated differences in environmental factors that affect the existence of Lauraceae species. Leaf venation studies support clustering in the family using characters such as primary, secondary, tertiary veins, and areola. Observation of leaf venation can be used as a taxonomic significance in the family Lauraceae. Epidermal cell walls in leaf samples are straight, curved shallow, deep, and sharp. Other characters that can be found are anomocytic, laterocytic, and brachyparasitic types of stomata, with stellate and glandless trichomes The anatomical dendrogram separated Lauraceae into clusters on a similarity coefficient scale.